مشكلات في تعلم علم الكلام من منظور النظرية الاجتماعية اللغوية - Adz Dzaki, Nuzulatul Akmaliyah (Maliki Interdisciplinary Journal, 2025)
Learning maharah kalām (Arabic speaking skills) is an important aspect of Arabic language teaching, especially to support the understanding of religious texts and daily communication. However, this learning process still faces various problems that can hinder learners’ mastery, especially in the context of being a foreign language. This article aims to examine the problems of kalām learning from a sociolinguistic perspective. By using descriptive qualitative method through literature study and content analysis, this study found that the barriers to kalām learning are influenced by various internal and external factors, such as mother tongue interference, code-mixing, lack of motivation, and lack of Arabic-speaking environment. Social and cultural factors, dialect differences, and learning approaches that are not contextualized also complicate the teaching process. Therefore, the solutions offered include the integration of the sociolinguistic approach in the curriculum, the creation of a supportive language environment, teacher training, and instilling a positive attitude towards Arabic. This approach that takes into account social aspects is expected to increase the effectiveness of kalām learning and learners’ language skills as a whole.